PENGARUH MOTIVASI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN DI PT ALAMJAYA WIRASENTOSA DEPO PEMATANGSIANTAR - Hutabarat, Defi Mariani; Lie, Darwin; Butarbutar, Marisi; Sisca, Sisca (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
As for this research problem formula is how To determine the influence of motivation and career development on employee job satisfaction in PT Alamjaya Wirasentosa Depo Pematangsiantar. Research Method used in this writing is library research and field research. The population in this research is the employee of PT Alamjaya Wirasentosa Depo Pematangsiantar which are 24 employees. The Data used is data by qualitative and quantitative, and technique of data collecting by questionnaires, interview and documentation. Then technique analyse the data use the descriptive method qualitative and quantitative descriptive method.Result of analysis from linear regresi modestly that is Å¶ = 16,518 + 0,402 X1 + 1,011 X2meaning there are positive influence between motivation and career development on employee job satisfaction. The strength of relationship between the variables is very strength, that is r= 0,843. From coefficient determinasi can explainable high and low of customerâ€™s purchase decision 71,9 %, and the rest 28,1 % explained by other factor which is not discussed in this research. From result of processing and calculation questionnaires, writer get the conclusion that motivation and career development have positive and significant impact on employee job satisfaction in PT Alamjaya Wirasentosa Depo Pematangsiantar. This matter is proved by hypothesis test either simultaneously where result test the fhitung (26,888) > ttabel (3,47) and which significant 0,000 < alpha 0,05.Â Keywords: Motivation, Career Development and Employee Job SatisfactionÂ